Evidence. The real diversity : Third Annual Exhibition of the Soros Center for the Arts Sofia. - Balkanski, Kamen; Boyadzhiev, B.; Kandinsky, Wassily; Stefanov, Svilen (Sofia : Soros Center for the Arts, 1996)
Boyadjiev, Bojidar ; Zankov, Ventsislav ; Gatev, Galentin ; Rouzhev, Georgi ; Toushev, George ; Grozdanov, Didmiter ; Kiuranov, Ivan ; Serapionov, Kalin ; Boyadjiev, Lutchezar ; Kostov, Liuben ; Solakov, Nedko ; Ivanov, Pravdoliub ; Kristev, Rassim ; Zekov, Roumen
biografie
Evidence. The real diversity : Third Annual Exhibition of The Soros Center for the Arts - Sofia City Gallery, Sofia, November 14 - December 7 1996
Engels & Bulgaars
boek